ANALYSIS OF THE QUALITY OF ROOT CANAL OBTURATION AND PREVALENCE OF APICAL PERIODONTITIS IN ENDODONTICALLY TREATED TEETH - Cristina Coralia Nistor; Ioana Suciu; Elena Zabrac; Ruxandra Ioana Bartok; Bogdan Dimitriu; Andreea Băluță (Romanian Journal of Oral Rehabilitation)
Aim: Our study aimed to identify the procedural errors of endodontic treatment and to establish the prevalence of apical periodontitis (AP) in root canal treated teeth by means of cone-beam computed tomography (CBCT). Material and method: There were a total of 604 treated permanent teeth. We looked for apical radiolucency and errors, such as: incomplete filling, missed canals, instrument fracture, perforation, overfilling, non-homogeneous fillings. Results. The overall prevalence of AP was 58.6%. The most frequent error was incomplete filling (42.88%), followed by low-density fillings (34.1%), missed canals (26.32%), overfilling (15.72), perforations (3.8%), fractured instruments (2.64%). Risk factors identified that were significantly associated with AP were: incomplete filling more than 2 mm, missed canals, perforations, non-homogeneous fillings, fractured instruments, tooth type (posterior) and cast posts. Conclusions. Prevalence of AP in endodontically treated teeth in this study was high. Poor quality root canal obturations were associated with post-treatment apical disease. CBCT is a precise imaging diagnostic tool and accurately highlights the technical parameters of the canal obturation, but also the presence of AP even in the early stages.